Gas turbine transient performance simulation, control and optimisation - Li, Zhou (Cranfield University, 2016)
A gas turbine engine is a complex and non-linear system. Its dynamic response changes at different operating points. The exogenous inputs: atmospheric conditions and Mach number, also add disturbances and uncertainty to the dynamic. To satisfy the transient time response as well as safety requirements for its entire operating range is a challenge for control system design in the gas turbine industry. Although the recent design of engine control units includes some advanced control techniques to increase its control robustness and adaptability to the changing environment, the classic scheduling technique still plays the decisive role in determining the control values due to its better reliability under normal circumstances. Producing the schedules requires iterative experiments or simulations in all possible circumstances for obtaining the optimal engine performance. The techniques, such as scheduling method or linear control methods, are still lack of development for control of transient performance on most commercial simulation tools. Repetitive simulations are required to adjust the control values in order to obtain the optimal transient performance. In this project, a generalised model predictive controller was developed to achieve an online transient performance optimisation for the entire operating range. The optimal transient performance is produced by the controller according to the predictions of engine dynamics with consideration of constraints. The validation was conducted by the application of the control system on the simulated engines. The engines are modelled to component-level by the inter-component volume method. The results show that the model predictive controller introduced in this project is capable of providing the optimal transient time response as well as operating the engine within the safety margins under constant or varying environmental conditions. In addition, the dynamic performance can be improved by introducing additional constraints to engine parameters for the specification of smooth power transition as well as fuel economy.
Keywords: Transient performance optimisation; inter-component volume (ICV) method; online system identification; recursive least squares (RLS); constrained model predictive control (MPC); gas turbine simulation